Simulating Fuzzy Systems - Buckley James J (Berlin Springer-Verlag, 2005)
Simulating Fuzzy Systems demonstrates how many systems naturally become fuzzy systems and shows how regular (crisp) simulation can be used to estimate the alpha-cuts of the fuzzy numbers used to analyze the behavior of the fuzzy system. This monograph pr
Keywords: Fuzzy systems